VURD Syndrome Managed by Pyelostomy - Charles J. Rosser; Sam Auringer; R. L. Kroovand (The Scientific World Journal)
We report a case of VURD syndrome in a three day old neonate who was diagnosed with hydronephrosis on a prenatal ultrasound. Severe tortuosity and dilation of the upper urinary tracts in the presence of progression of hydronephrosis or a persistently elevated creatinine may favor a proximal urinary diversion rather than primary valve ablation or cutaneous vesicostomy. Because of a persistently elevated serum creatinine, a nonfunctioning kidney with grade 4/5 vesicoureteral reflux and worsening contralateral hydronephrosis despite lower tract drainage, a left cutaneous pyelostomy was performed, contralateral to the kidney involved with VURD. Postoperatively the serum creatinine stabilized at 1.0 mg/dl and decreased to 0.3 mg/dl at one month of age.